2020
DOI: 10.3390/genes11020170
|View full text |Cite
|
Sign up to set email alerts
|

Homology-Free Detection of Transposable Elements Unveils Their Dynamics in Three Ecologically Distinct Rhodnius Species

Abstract: Transposable elements (TEs) are widely distributed repetitive sequences in the genomes across the tree of life, and represent an important source of genetic variability. Their distribution among genomes is specific to each lineage. A phenomenon associated with this feature is the sudden expansion of one or several TE families, called bursts of transposition. We previously proposed that bursts of the Mariner family (DNA transposons) contributed to the speciation of Rhodnius prolixus Stål, 1859. This hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…The unique specimen was found very damaged in Sergipe state, Brazil, a region included in the distribution range of R. domesticus, therefore, examination of further material is essential to confirm whether or not R. zeledoni is a valid species. Following Monteiro et al (2018), R. marabaensis dos Santos Souza et al, 2016 has been suggested to be a genetic variant very close to R. robustus Larrousse, 1927 (specific status recently considered valid by Castro et al, 2020) and R. taquarussuensis (Rosa et al, 2017), was synonymized with R. neglectus Lent, 1954by Nascimento et al (2019 based on interspecific crosses and molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…The unique specimen was found very damaged in Sergipe state, Brazil, a region included in the distribution range of R. domesticus, therefore, examination of further material is essential to confirm whether or not R. zeledoni is a valid species. Following Monteiro et al (2018), R. marabaensis dos Santos Souza et al, 2016 has been suggested to be a genetic variant very close to R. robustus Larrousse, 1927 (specific status recently considered valid by Castro et al, 2020) and R. taquarussuensis (Rosa et al, 2017), was synonymized with R. neglectus Lent, 1954by Nascimento et al (2019 based on interspecific crosses and molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…According to the annotation of this genome assembly, the repeatome of R. prolixus —repeated DNA sequences composing a genome [ 3 ]—make up to 5.6% of the genome, with Class II transposable elements being the main components [ 1 ]. Recently, Castro et al [ 4 ] applied dnaPipeTE software [ 5 ] to re-evaluate the transposable element (TEs) quantification in the R. prolixus genome, with astonishing results. Using the same raw data obtained in the genome assembly project, Castro et al [ 4 ] estimated that the amount of TEs in the R. prolixus genome ranged between 19% and 23%, that is, three to four times higher than the original quantification of Mesquita et al [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Castro et al [ 4 ] applied dnaPipeTE software [ 5 ] to re-evaluate the transposable element (TEs) quantification in the R. prolixus genome, with astonishing results. Using the same raw data obtained in the genome assembly project, Castro et al [ 4 ] estimated that the amount of TEs in the R. prolixus genome ranged between 19% and 23%, that is, three to four times higher than the original quantification of Mesquita et al [ 1 ]. In addition, they evaluated other sibling species, R. montenegrensis and R. marabaensis (formerly R. robustus II and III, respectively [ 6 ]), with similar results.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was concluded that R. montenegrensis and R. robustus clade II are in all likelihood the same species [127]. However, the repeatome and proteomic analyses detected high differentiation between R. prolixus, R. montenegrensis, and R. marabaensis, showing they are different species [144,145].…”
Section: The Advent Of Genomic Data: Genomics and Transcriptomics In The Rhodniniimentioning
confidence: 59%